Blood Requisition and Utilization Practice in Surgical Patients at University of Gondar Hospital, Northwest Ethiopia. (28th November 2013) - Belayneh, Tadesse; Messele, Gashaw; Abdissa, Zewditu; Tegene, Birehanemeskel
Abstract : Background. Although blood ordering is a common practice in surgical field, the average requirement for a particular procedure is usually based on subjective anticipation of blood loss rather than on evidence based estimates. Overordering with minimal utilization squanders technical time, reagent and imposes extra expenses on patients. This study was conducted to assess blood utilization practices. Methods . Cross-sectional study was conducted in Gondar Hospital. Five-month data were collected from all discharged surgical patients and blood bank registries. Blood utilization was calculated using crossmatch to transfusion ratio (C/T), transfusion probability (%T), and transfusion index (TI) indices. Results. A total of 982 patients were requested to prepare 1, 072 crossmatched units. Of these, 468 units were transfused for 286 patients. The overall ratios of C/T, %T, and TI index were 2.3, 47%, and 0.77, respectively. Blood transfusion from the units crossmatched was 43.6%. Moreover, the highest C/T ratio was observed in elective surgical patients. Conclusions. The overall blood utilization was encouraging, but excessive crossmatching with minimal transfusion practice was observed in elective surgical patients. Blood ordering pattern for elective procedures needs to be revised and overordering of blood should be minimized. Moreover, the hospital with blood transfusion committee should formulate maximum surgical blood ordering policies for elective surgical procedures and conduct regular auditing.